Preiser disease after repeated local glucocorticoid injections: A case report - Tomori, Yuji (Medicine (Baltimore), 2018)
RATIONALE: Preiser disease or avascular necrosis (AVN) of the scaphoid causes intolerable wrist pain and malalignment of the carpal bones. In previously reported cases, patients have had a history of steroid use for systemic illness such as autoimmune hemolytic anemia, systemic lupus erythematosus, or renal transplantation, or have had other risk factors, such as smoking, alcoholism, or infection. In particular, systemic glucocorticoid therapy has been most commonly associated with the disease. Although there are reports of AVN of the scaphoid induced by systemic glucocorticoids, no prior report has associated AVN of the carpal bones with repeated local injections of glucocorticoids. PATIENT CONCERNS: We present a case in which it was strongly suspected that AVN of the scaphoid was induced by repeated local glucocorticoid injections. The patient had no history of excessive alcohol use, smoking, or trauma, except for local repeated steroid injections. DIAGNOSES: Initially, she had diagnosed with de Quervain's disease and was treated by repeated local glucocorticoid injections followed by surgery for de Quervain's disease. Five years after surgery for de Quervain's disease, the patient presented at our hospital with sudden onset of intolerable pain in her right wrist without a history of trauma. In spite of nonsurgical treatment with rest, immobilization, analgesia, and surgery, her wrist pain was not improved. After further repeated local steroid injections in her wrist, radiographs, and magnetic resonance imaging of her wrist showed the AVN of the scaphoid. INTERVENTIONS: Surgery was performed and the fragmented proximal scaphoid and the entire lunate were resected. OUTCOMES: The diagnosis was confirmed according to the histopathological examination of the proximal scaphoid bone, which showed the characteristic of AVN of the scaphoid. At follow-up evaluation, radiographs of the right wrist showed no progression of osteoarthritis. The patient had no tenderness or residual pain at the wrist and had no desire to pursue additional surgery. LESSONS: We have presented a case with AVN of the scaphoid, which was strongly suspected to be associated with the repeated local steroid injections. Further studies are required to more fully elucidate the association between AVN of the scaphoid and repeated local steroid injections.